An extensive survey of Bemisia tabaci (Homoptera: Aleyrodidae) in agricultural ecosystems in Florida - McKenzie, CL; Anderson, Pamela K.; Villarreal, N. (Florida Entomological Society, 2004)
An extensive survey of B. tabaci populations in 15 economically important crops and 8 weed species in Florida was carried out from March 2000 through May 2001. Sex ratios did not significantly differ among host plants. Biotype analysis by RADP/PCR indicated the presence of only the B biotype of B. tabaci in all collections. These data suggest that in Florida the B biotype of B. tabaci has excluded the native non-B biotypes in agricultural ecosystems.